KAJIAN AKTIVITAS FARMAKOLOGI DAN MEKANISME AKSI POLIHERBAL EKSTRAK PEGAGAN, MENIRAN, DAN KENCUR: LITERATURE REVIEW: Review Article - Santoso, Rahmat Santoso (Jurnal Komunitas Farmasi Nasional, 2024)
Plants, as natural sources of food, herbs, and medicines, have been used for thousands of years in many traditional healing systems. In both developed and developing countries, the use of herbal plants to treat various diseases and the research into products with their properties have increased rapidly. Although there is already a vast amount of literature, aspects such as phytochemistry, pharmacological activity, and mechanisms have not been reviewed comprehensively. This review article aims to provide a collection of information about selected herbal plants, namely Meniran (Phyllanthus niruri Linn.), Gotu Kola (Centella asiatica (L.) Urban), and Kencur (Kaempferia galanga L.). In compiling this review article, the literature study method from collections of national and international journals was used. Based on the resulting literature survey, it can be concluded that there are still few journals that discuss aspects of these plants, especially the mechanisms of action.Keywords: Phyllanthus niruri, Centella asiatica, Kaempferia galanga, Pharmacological activity, Mechanisms of action, and Phytochemistry.